Real-world study on adverse drug reactions of pembrolizumab in endometrial cancer treatment: insights from the FAERS database - Zhang, Huiping; Di, Man; Wang, Jingjing; Wang, Shan; Dai, Yini; Huang, Jingjing; Zhou, Zhuo (Frontiers in Pharmacology, 2025)
ObjectivePembrolizumab is a key drug in the immunotherapy of endometrial cancer (EC) and has improved the prognosis to some extent. However, adverse drug events (ADEs) have hindered the achievement of expected therapeutic outcomes in EC. This study, therefore, aims to investigate the ADEs of pembrolizumab using the FAERS database, offering new insights for clinical practice in EC treatment.MethodFrom the first quarter of 2016 to the first quarter of 2025, ADEs associated with pembrolizumab in EC were collected from the FAERS database. The Reporting Odds Ratio (ROR) was used as the primary analytical method for signal detection. To validate the robustness of the results, three additional algorithms—Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-Item Gamma Poisson Shrinker (MGPS)—were also applied. ADEs were systematically classified using the Medical Dictionary for Regulatory Activities (MedDRA) into System Organ Classes (SOC) and Preferred Terms (PT), and ranked by both frequency and signal strength.ResultsA total of 2,154 ADEs associated with pembrolizumab in the treatment of EC were retrieved from the FAERS database. The age distribution of ADEs was primarily concentrated in the 65–85 years age group. The reported body weights were mainly in the 50–100 kg range. The most frequent ADE outcome was hospitalization. The majority of ADEs occurred within 0–30 days after pembrolizumab administration. Identified ADEs involved endocrine system disorders, including Increased Thyroid Hormones (ROR = 9.22), Decreased Thyroid Hormones (ROR = 5.31), and Immune-Mediated Hypothyroidism (ROR = 6.16). Skin and subcutaneous tissue disorders included Pruritic Rash (ROR = 3.16) and Blisters (ROR = 3.06). Liver-related issues included Increased Hepatic Enzymes (ROR = 2.25). These key signals were consistently confirmed by additional disproportionality algorithms, including PRR, BCPNN, and MGPS, reinforcing the robustness of the findings.ConclusionThis study used the FAERS database to identify frequently reported ADEs associated with pembrolizumab in the treatment of EC, including endocrine system diseases, musculoskeletal system disorders, skin and subcutaneous tissue reactions, and hepatotoxicity. These findings provide crucial evidence for risk stratification and safety monitoring in clinical practice, emphasizing the need for vigilance toward specific organ systems during the 0–30-day treatment window.